Effect of the ambient conditions on the operation of a large-area integrated photovoltaic-electrolyser. Issue 9 (30th July 2020) - Kemppainen, Erno; Aschbrenner, Stefan; Bao, Fuxi; Luxa, Aline; Schary, Christian; Bors, Radu; Janke, Stefan; Dorbandt, Iris; Stannowski, Bernd; Schlatmann, Rutger; Calnan, Sonya
Abstract : Temperature affects the efficiency of an integrated photovoltaic-electrolyser significantly more than the photovoltaic cells alone. Abstract : An integrated photovoltaic-electrolyser with a solar collection area of 294 cm 2 was constructed and its performance, represented by the solar to hydrogen (STH) conversion efficiency and hydrogen production rate m H2 in various outdoor and indoor conditions, was investigated by measurements of the product gas streams. The device was composed of silicon heterojunction photovoltaic cells integrated with an electrolysis cell using nickel foam electrodes coated with nickel iron oxide and nickel molybdenum on the anode and cathode side, respectively, with 1.0 M KOH electrolyte. Depending on the operating conditions, the STH efficiency was typically 3.4–10% and typical m H2 of 30–60 mg h −1, approximately corresponding to 1–2 W output power. When considering non-concentrating devices, the STH efficiency is one of the best for solar collection areas exceeding 100 cm 2 and the hydrogen production rate the highest reported for devices smaller than 1 m 2 . The efficiency seems to depend mainly on the temperature, and less on the irradiance, reducing at a rate of about 0.35% (absolute) per 1 °C increase in ambient temperature, significantly steeper than the efficiency of the used photovoltaic cells, making it a possible concern for practical hydrogen generation.